Public Participation Provisions in Environmental Impact Assessment process in Ethiopia: A Comparative Analysis - Gezahegn, Melaku (Bahir Dar University Journal of Law, 2022)
The Constitution of the Federal Democratic Republic of Ethiopia and relevant subsidiary laws grant people the right to full consultation and to the expression of views in the planning and implementation of environmental policies. However, the impact of these general principles on the desired outcome is limited, suggesting the need for formulation of further detailed rules. Particularly, an effective realization of such constitutional stipulations require detailed rules that clearly set out identification of legitimate stakeholders, mechanisms of information accessibility, information dissemination, grievances handling processes, timeline to review and make comments, incorporation of public comments into final Environmental Impact Assessment (EIA) decisions. The objective of this article is to comparatively assess and explain the sufficiency and lacunas of the existing Public Participation Provisions (PPPs) of Ethiopia against countries having detailed rules required for the realization of effective public participation. To this end, a doctrinal research method is used to assess the content, principles and gaps in the existing legal documents. It is argued in the article that the existing environmental laws of Ethiopia are short of providing the required PPPs rules ranging from identification of stakeholders to grievance handling mechanisms. This in fact would render public participation to be a mere procedural requirement than creating an avenue for the public to influence environmental decision making processes. The assessments conducted thus uncover the dire need for the enactment of detailed PPPs and the possible ways to achieve this.